2016
DOI: 10.1038/ncomms11184
|View full text |Cite
|
Sign up to set email alerts
|

Super-complexes of adhesion GPCRs and neural guidance receptors

Abstract: Latrophilin adhesion-GPCRs (Lphn1–3 or ADGRL1–3) and Unc5 cell guidance receptors (Unc5A–D) interact with FLRT proteins (FLRT1–3), thereby promoting cell adhesion and repulsion, respectively. How the three proteins interact and function simultaneously is poorly understood. We show that Unc5D interacts with FLRT2 in cis, controlling cell adhesion in response to externally presented Lphn3. The ectodomains of the three proteins bind cooperatively. Crystal structures of the ternary complex formed by the extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 68 publications
4
107
0
Order By: Relevance
“…On the other hand, Cntn6 is known to complex with other membrane proteins as well, including Ptpra, Ptprg, PTPσ, Notch, and Chl1 (Cui et al, 2004; Hu et al, 2006; Ye et al, 2008; Bouyain and Watkins, 2010; Zuko et al, 2011). A case in which cell adhesion proteins form super-complexes with competing components has recently been made for Lphn3 association with Flrt and UncD members at the structural and functional level (Jackson et al, 2016). In the protein interaction repertoire of Lphn1 other ASD gene products are known to be present, in particular, Nrxn1 which is a major ASD gene interacting with Nlgn1 and LRRTMs (Ichtchenko et al, 1995; de Wit et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Cntn6 is known to complex with other membrane proteins as well, including Ptpra, Ptprg, PTPσ, Notch, and Chl1 (Cui et al, 2004; Hu et al, 2006; Ye et al, 2008; Bouyain and Watkins, 2010; Zuko et al, 2011). A case in which cell adhesion proteins form super-complexes with competing components has recently been made for Lphn3 association with Flrt and UncD members at the structural and functional level (Jackson et al, 2016). In the protein interaction repertoire of Lphn1 other ASD gene products are known to be present, in particular, Nrxn1 which is a major ASD gene interacting with Nlgn1 and LRRTMs (Ichtchenko et al, 1995; de Wit et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The ECRs of other aGPCRs are major players in mediating receptor functions as well. For example, using its ECR, ADGRA2/GPR124 regulates isoformspecific Wnt signaling [77][78][79][80] , the C. elegans ADGRL1/LAT-1 controls cell division planes during embryogenesis, and ADGRB1/BAI1 and ADGRL3/Lphn3 mediate synapse formation through interaction with other cell-surface proteins [81][82][83][84] . Thus, the ECRs of other aGPCR family members are also promising drug targets to treat numerous diseases once mechanistic details about their regulatory functions are understood.…”
Section: Discussionmentioning
confidence: 99%
“…S2B) may be due to a loss of cell responsivity to LPHN2 ligands endogenously produced by ECs themselves, such as FLRT1-3 proteins (Seiradake et al, 2016). Indeed, the ectodomains of transmembrane FLRTs (Jackson et al, 2016) can be shed and act in vivo as repulsive factors capable of steering both axons (Yamagishi et al, 2011) and blood vessels (Seiradake et al, 2014). By means of real-time quantitative reverse transcription PCR (qRT-PCR) analysis, we observed that cultured human umbilical vein ECs actively transcribe FLRT2, but neither FLRT1 nor FLRT3 genes ( Fig.…”
Section: Resultsmentioning
confidence: 99%